Prototipe Pemantauan Level Air Pada Bendungan Berbasis IOT - Mardhiyah Nas; Misnawati; Megha Rahmawaty Marsing; Fadlia (Journal of Applied Smart Electrical Network and Systems, 2020)
The purpose of making this prototype is to make a water level pemantauan tool in the dam using ultrasonic sensors and an IoT system. To support the manufacture of this tool, several other electronic components are used, including the NodeMCU microcontroller, ultrasonic sensors, water pumps, relays, and buzzers. The process of the water level pemantauan system in the IoT-based dam works as a whole. The process begins with filling water from box 1 (analogous to river) to box 2 (analogous to a dam) assisted by a water pump to fill the water box. Then the ultrasonic sensor reads the water distance data from the dam and is sent to the microcontroller and then displayed on ThingSpeak via PC / HP. When box 2 is filled with water and reaches the maximum limit, the buzzer will sound and the relay will turn off the water pump automatically. The test results show that the data obtained is accurate. When the sensor reads the water level capacity data at a distance of 6 cm, the dam capacity will be fully read, the buzzer will sound and turn off the relay automatically then send the information to ThingSpeak. Reading or pemantauan the water level in the dam can be an alternative to control the water level in the dam and facilitate the dam guard.